2006
DOI: 10.1159/000095486
|View full text |Cite
|
Sign up to set email alerts
|

Reasons for Tooth Extraction in Kuwait

Abstract: Objectives: To investigate reasons for tooth extraction and its association with age and gender in Kuwait. Subjects and Methods: A record of all tooth extractions performed in 21 general dental practice centers during a 1-month period was logged on specially designed study forms. The patient’s age and gender, number of teeth extracted, and the reason(s) for the extraction were recorded. Results: A total of 2,783 teeth were extracted in 1,604 patients (1.73 ± 0.07 teeth per patient). Caries and periodontal dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

26
85
5
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(131 citation statements)
references
References 54 publications
26
85
5
3
Order By: Relevance
“…However, our percentage of permanent-tooth extraction due to caries was higher than that indicated in the previous studies. Also, all of the previous studies [3,4,7,15,16] indicated that periodontal disease was the secondmost common reason for extraction, which is different from our results. The reason forthis difference cannot be identifiedby our results.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…However, our percentage of permanent-tooth extraction due to caries was higher than that indicated in the previous studies. Also, all of the previous studies [3,4,7,15,16] indicated that periodontal disease was the secondmost common reason for extraction, which is different from our results. The reason forthis difference cannot be identifiedby our results.…”
Section: Discussioncontrasting
confidence: 99%
“…Our results are similar to the findings in previous literature forthe same Arabic region [7,15,16] and internationally [3,4],whichindicate that caries is the most common cause underlyingextraction. However, our percentage of permanent-tooth extraction due to caries was higher than that indicated in the previous studies.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In our study, the most common reason for tooth loss was periodontal disease, especially in group III subjects, but in group I subjects, the common reason was dental caries. This is in accordance with studies done by AlShammari et al 15 where caries was the primary reason for tooth loss in patients with age <40 years, whereas in patients with more than 40 years of age, periodontal disease was the most common reason. Partially edentulous state was again more prevalent in group III subjects compared with groups I and II.…”
Section: Discussionsupporting
confidence: 93%